Smart City dan Perubahan Komunikasi Publik: Tantangan dan Peluang Bagi Pemerintah dan Masyarakat - Basit, Abdul; Nurlukman, Adie Dwiyanto (Avant Garde, 2023)
Tangerang City is a city that has developed rapidly in recent years. The industrial area in this city is one of the causes of significant economic growth. Apart from that, good road infrastructure and easy accessibility to Soekarno-Hatta international airport are also factors that facilitate access and mobility to this city. In recent years, the city of Tangerang has also begun to introduce the smart city concept by utilizing information and communication technology to improve public services and the quality of life of the community. This research uses a quantitative approach, explanatory research, with a sample of 100 people. The research results obtained are that communication technology variables (X) on public communication (Y) on service quality (Z) influence each other or the hypothesis is accepted. The smart city concept is an intelligent and in-depth approach to information technology and public services to build a dream city, integrated in nature to solve city problems such as population growth, ICT infrastructure, economic, political, cultural problems and the changes in government paradigms. Information and communication technology as a solution to problems that have occurred so far and become facilitators, mediators and interpreters between organizations and the public. Communication technology allows faster and wider access to information.